Estadiamento, genótipos de HPV e metilação do gene WIF1 em câncer do colo do útero: associações com o prognóstico e sobrevida - Carvalho, Keila Patrícia Almeida de (2016)
Introduction. Squamous cell carcinoma is the most common type of cervical cancer, followed by endocervical adenocarcinoma. Tumor staging is important to evaluate prognosis. Cervical infection by one of the oncogenic types of HPV, especially HPV 16 and 18 is a pre-requisite for developing invasive cancer. Epigenetics alterations, as DNA methylation, are well-known carcinogenic mechanisms. WIF1 is a tumor suppressor gene which silencing by methylation helps in neoplastic progression. Objective. The goal of this study was to evaluate staging, HPV genotypes and WIF1 methylation in cervical cancer and to test association between these variables with age, prognosis and survival. Methods. It was included 95 cases obtained in Araujo Jorge Hospital (Goiânia/ GO): 73 of invasive squamous cell carcinoma and 22 of invasive endocervical adenocarcinoma. DNA was extracted from paraffin-embedded biopsies using phenol-chloroform. HPV detection and genotyping were conducted using the kit INNO- LiPA HPV GENOTYPING EXTRA® (Innogenetics™). Methylation of WIF1 gene was evaluated by methylation-specific PCR (MSP). Odds Ratio was used to calculate statistical association. The calculation of survival used the Kaplan-Meier method and the log-hank test was used to compare means of survival and prognostic factors. A value of p<0.05 was considered statically significant. Results. There was significant association between tumor stages III and IV and worse prognosis (OR = 7.32). The 5-year overall survival was 79.1% and it was significant higher in cases with tumor stages I and II (p = 0.001). Women between 50 and 60 years had more chances having tumors in stages III and IV (OR = 0.15). Although, considering mean and median ages of women included, those over 51 years were more likely having tumor stages III and IV (OR = 5.92). No association was found between worse prognosis or lower survival and histological type, HPV infection and WIF1 methylation. Conclusion. Worse prognosis and lower survival was determined by tumor stages III and IV.